Vibranium and Technological Hybridity: Neo-Colonial Anxiety in Black Panther - Anggy Rahayu Larasati; E. Ngestirosa Endang Woro Kasih (Universitas Negeri Semarang, 2026)
This study aims to analyze the film Black Panther (2018) through Homi K. Bhabha’s postcolonial concepts of hybridity, ambivalence, and the Third Space to explore the negotiation of identity, technology, and power within an African context. Using a qualitative-descriptive method, this research examines selected dialogues and narrative scenes to reveal how the film constructs ideological tensions between T’Challa and Killmonger as two responses to colonial trauma reform and radical resistance. Vibranium functions not only as a source of technological advancement but also as a symbolic site of neo-colonial anxiety. Furthermore, Wakanda emerges as a hybrid state that embodies both cultural heritage and modern progress, while exposing the vulnerabilities of postcolonial nations to global exploitation. The findings suggest that Black Panther transcends the conventional boundaries of the superhero genre, offering a critical reflection on technological hybridity, racial identity, and postcolonial futures in the era of globalization.